Clinical Features and Management of Pancreatic Solid Pseudopapillary Tumor. Issue 12 (December 2014) - Tsukamoto, Masayo; Hashimoto, Daisuke; Chikamoto, Akira; Abe, Shinya; Ohmuraya, Masaki; Baba, Hideo
Solid pseudopapillary tumor (SPT) is a rare pancreatic tumor with low malignant potential. Between February 2006 and May 2013, six patients were affected by SPT. Two patients were male and four were female. Median age of the patients was 31.5 years (range, 13 to 47 years). One patient was preoperatively diagnosed by an endoscopic ultrasound-guided fine-needle aspiration biopsy. Pancreaticoduodenectomy was performed in two and distal pancreatectomy was done in four. One operation of those was laparoscopic distal pancreatectomy. In this series, recurrence or distant metastasis was not reported and successful outcome was achieved in all patients. In conclusion, whereas diagnosis of SPT is difficult, it can be diagnosed by endoscopic ultrasound-guided fine-needle aspiration biopsy preoperatively. It should be treated by surgery, and laparoscopic operation can be considered.